Study of 5-Aryl-Furan Derivatives as a Corrosion Inhibitor for Mild Steel in 0.1 N HCl Solution - Satarkar, S.; Dubey, R. S. (Journal of Scientific Research, 2025)
In 0.1 N HCl solution, 5-[4-bromophenyl]-furan-2-carbaldehyde and 5-[4-chlorophenyl]-furan-2-carbaldehyde, two derivatives of furan, were synthesized and used as corrosion inhibitors for mild steel. The effectiveness of the inhibition of both inhibitors was investigated using surface analytical, electrochemical, and gravimetric techniques. It was discovered that both inhibitors' inhibition efficiency increased and their corrosion rate decreased as the quantities of the inhibitors were increased. The maximum inhibitory efficiencies were 92.10 % and 89.47 % for 5-[4-bromophenyl]-furan-2-carbaldehyde and 5-[4-chlorophenyl]-furan-2-carbaldehyde, respectively, at 600 ppm concentration. As the temperature increased, the inhibition effectiveness decreased for both inhibitors. The finding of the electrochemical study that the two inhibitors used are mixed types was supported by both physical and chemical adsorption data. The findings of the gravimetric study best matched the Langmuir Adsorption Isotherm. The results of the gravimetric and electrochemical analyses showed a significant connection. SEM and EDAX studies were used to confirm the passive film that formed on the metal surface.